Geochemical Characteristics of Catalytic Hydrogenation of Low-Mature Kerogen Under Deep Fluids - Huang, Xiaowei; Jin, Zhijun; Liu, Quanyou; Meng, Qingqiang; Zhu, Dongya; Wang, Lu; Liu, Jiayi; Zhang, Panpan; Wang, Jingbin (Frontiers in Earth Science, 2022)
There is increasingly valued attention on whether the matter and energy carried in the deep fluids can significantly change the hydrocarbon (HC) generation of low-mature source rocks. Previous studies suggest that the upward movement of deep fluids to sedimentary basins will change the HC generation evolution mode of low-mature source rocks, and the matter and energy carried by the fluid will transform the evolution process as transient events. However, there is a lack of quantitative evaluation of the specific changes of gaseous HC generation in the process of modification. In this study, the effect of deep fluids on HC generation and evolution of low maturity source rocks were quantitatively studied through simulation experiments of the gold tube closed system. We quantitatively selected hydrogen and catalysts (ZnCl2 and MoS2) to conduct catalytic hydrogenation of kerogen and explore the quantitative effects of deep fluids on HC generation in low-mature source rocks. Through the experimental results, it is found that catalytic hydrogenation has significant changes in a HC generation transformation of organic matter (OM). With the increase of catalytic hydrogenation reaction intensity, the maximum gaseous HC generation yield is 3.16-3.24 times that of the control groups without hydrogenation. In the relatively low-temperature stage (< 400℃), the competitive hydrogenation effect occurs and the drying coefficient is high. After the high-temperature stage, a large amount of hydrogen participates in the reaction, which significantly promotes the increase of gaseous HCs and decreases the drying coefficient. ZnCl2 or MoS2 can change the relative content ratio of isomerism and isomorphism of butane and pentane, suggesting that cationic catalysis plays a greater role. In the reaction process, OM plays the most important role in the contribution to HC generation, exogenous hydrogen is more likely to participate in HC generation reaction than water and has the potential contribution to HC generation in Fischer-Tropsch synthesis (FFT) under catalytic conditions. The results of this study effectively verify that exogenous hydrogen and metal elements in deep fluids significantly modify the thermal evolution of low-mature source rocks, and enhance the HC generation potential in the high-temperature stage.